HIV and syphilis epidemic among MSM and non-MSM aged 50 and above in Shanghai, China: A yearly cross-sectional study, 2008–2014. Issue 11 (2nd November 2018) - Ning, Zhen; Fu, Jie; Zhuang, Minghua; Park, Jason A.; Ibragimov, Umedjon; He, Na; Wong, Frank Y.
ABSTRACT: The magnitude of the HIV and syphilis epidemic among Chinese men ages 50 and older is unclear. In this study, we aimed to characterise and compare the prevalence of HIV and syphilis infections; linkage to care among those infected with HIV; and the geographic distribution of the two epidemics among elderly men who have sex with men (MSM) and non-MSM in Shanghai, China. This cross-sectional study involved 12, 910 men ages 50 and above who participated in the HIV voluntary and counselling testing programme each year from 2008 to 2014. HIV prevalence among MSM in our sample ranged between 4.9% and 15.4%, while syphilis frequency among non-MSM decreased from 26.0% to 18.7%. Further, in 2014, MSM participants had a higher HIV prevalence than non-MSM (4.9% vs 1.8%), whereas syphilis was higher in older non-MSM compared to MSM (18.7% vs 12.4%). Among those infected with HIV, 121/211 (53.75%) of participants were linked to HIV treatment, where the linkage rate was comparable to that in Kunming [Zhao, S., Zhao, G., Zhang, W., liao, B., Chu C., Wang J., & Li, L. (2015). Compare the difference of efficiency between voluntary counseling testing and provider-initiated testing counseling for identifying HIV/AIDS in Kunming. Chinese Journal of AIDS & STD, 21 (7), 623-625]. The high burden of HIV and syphilis among men ages 50 and older in Shanghai, China highlights the need to target older Chinese men, both MSM and non-MSM, with prevention efforts.